Formas de vida e integración de los afroperuanos de hoy - Arroyo Aguilar, Sabino (2006)
In this ethnographic study we express the continuous visible presence of the Afroperuvians, linked to the economic political and religious life of the country; with impact on the cult to the «Lord. of Pachacamilla» that integrates the Andean, African-American, Hispanic and mestizo ethnic groups from colonial times down to the present. Even the cults to «Santa Efigenia» and «Kyrios Zulú» are more legitimate for descendents of Afroperuvians, although there is also a presence here of the Andeans and mestizos. In the same way, the «National Afroperuvian Movement «, the juvenile group of the «Makungu» and the NGOs, such as CEDET constitute institutions that are evidence of the vital force of emerging institutions, based on affirmation of their own culture, within the social structures and ethnic frontiers, and the networks of power of our pluriethnic and multicultural country, with a prevalence for galloping occidental modernity.